2003
DOI: 10.3168/jds.s0022-0302(03)74023-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evaluation of Fertility Using Direct and Correlated Traits

Abstract: Poor fertility has become a major reason for involuntary culling of dairy cows in the United Kingdom. Calving interval (CI) and body condition score (BCS) are recorded, heritable, genetically correlated with each other, and could be used to extend the scope of dairy indices to include fertility traits. The use of U.K. insemination information for the evaluation of fertility has not been examined previously. Fertility and correlated traits were examined using nationally recorded milk (MILK = daily milk yield at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
160
3
14

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 171 publications
(212 citation statements)
references
References 29 publications
(36 reference statements)
35
160
3
14
Order By: Relevance
“…The low heritability of the traditional fertility traits in the present study corroborates the many previous studies on genetic parameters for traditional fertility measures (Pryce and Veerkamp, 2001;Berry et al, 2003;Wall et al, 2003). The heritability estimates of CFH and CFS, however, are slightly larger than that generally observed from field data, which may be attributable to an expected greater accuracy of recording in experimental herds.…”
Section: Genetic Parameterssupporting
confidence: 88%
See 3 more Smart Citations
“…The low heritability of the traditional fertility traits in the present study corroborates the many previous studies on genetic parameters for traditional fertility measures (Pryce and Veerkamp, 2001;Berry et al, 2003;Wall et al, 2003). The heritability estimates of CFH and CFS, however, are slightly larger than that generally observed from field data, which may be attributable to an expected greater accuracy of recording in experimental herds.…”
Section: Genetic Parameterssupporting
confidence: 88%
“…Genetic correlations among the traditional fertility variables were generally similar to those estimated on primiparae in larger datasets (Wall et al, 2003). Nonetheless, the genetic correlations between the traditional fertility traits and CLA were different from those reported elsewhere, albeit the standard errors in the present study and in most of the other studies were large, attributable to a combination of low heritability of the fertility traits and the relatively small datasets.…”
Section: Genetic Parameterssupporting
confidence: 62%
See 2 more Smart Citations
“…Several studies have reported a longer calving interval in recent years than before, including studies in Canada (Murray, 2003), Spain (Gonzá lez-Recio et al, 2004), the Netherlands (Nederlands Rundvee Syndicaat (NRS), 2005) and the United Kingdom (Wall et al, 2003). According to Hare et al (2006a), the increase is about 1 day per year for Holsteins.…”
mentioning
confidence: 99%